PENGARUH PRENATAL GENTLE YOGA TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN DI MUTASANICARE TAHUN 2024 (Al-Insyirah Midwifery: Jurnal Ilmu Kebidanan (Journal of Midwifery Sciences), 2025)
Expectant mothers experiencing anxiety and stress can be significantly affected by the Hypothalamic-Pituitary-Adrenal (HPA) axis, which triggers the release of stress hormones such as ACTH (Adrenocorticotropic Hormone), cortisol, and catecholamines. Research shows that anxiety during pregnancy can be effectively reduced or even eliminated through recommended physical activities, specifically Prenatal Gentle yoga. This form of exercise is not only cheap and easy to do, but also offers substantial benefits to physical and psychological well-being. Statistical analysis yielded a paired sample test result with a p-value of 0.001, which is less than the 0.05 threshold. This indicates rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha), leading to the conclusion that Prenatal Gentle yoga has a significant positive impact in reducing anxiety levels among pregnant women in their third trimester as they prepare for delivery at Mutasicare in 2024
Keywords: Pregnant Women; Anxiety; Prenatal Gentle Yoga